Mitochondrial dysfunction and increased DNA damage in vascular smooth muscle cells of Abdominal Aortic Aneurysm (AAA-SMC) - Tavris, Bengi S.; Peters, Andreas; Böckler, Dittmar; Dihlmann, Susanne (Oxidative medicine and cellular longevity, 2023)
There is increasing evidence for enhanced oxidative stress in the vascular wall of abdominal aortic aneurysms (AAA). Mitochondrial damage and dysfunction are hypothesized to be actors in altered production of reactive oxygen species (ROS) and oxidative stress. However, the role of mitochondria and oxidative stress in vascular remodelling and progression of AAA remains uncertain. We here addressed whether mitochondrial dysfunction is persistently increased in vascular smooth muscle cells (VSMCs) isolated from AAA compared to healthy VSMC. AAA-derived VSMC cultures (AAA-SMC, ) and normal VSMC cultures derived from healthy donors () were grown in vitro and analysed for four parameters, indicating mitochondrial dysfunction: (i) mitochondrial content and morphology, (ii) ROS production and antioxidative response, (iii) NADP+/NADPH content and ratio, and (iv) DNA damage, in the presence or absence of angiotensin II (AngII). AAA-SMC displayed increased mitochondrial circularity (rounded shape), reduced mitochondrial area, and reduced perimeter, indicating increased fragmentation and dysfunction compared to healthy controls. This was accompanied by significantly increased O2- production, reduced NADP+/NADPH levels, a lower antioxidative response (indicated by antioxidative response element- (ARE-) driven luciferase reporter assays), more DNA damage (determined by percentage of γ-H2A.X-positive nuclei), and earlier growth arrest in AAA-SMC. Our data suggest that mitochondrial dysfunction and oxidative stress are persistently increased in AAA-SMC, emphasizing their implication in the pathophysiology of AAA.